ChemInform Abstract: Efficient Synthesis of 1, 5‐Disubstituted Carbohydrazones Using K2CO3 as a Carbonyl Donor. Issue 45 (23rd October 2014) - Wen, Jun; Yang, Chu‐Ting; Jiang, Tao; Hu, Sheng; Yang, Tong‐Zai; Wang, Xiao‐Lin
Abstract A novel method for the synthesis of carbohydrazones (III) via carbonylation of tosylhydrazones using K2CO3 as the carbonyl donor is developed.